Producing durable pellets from barley straw subjected to radio frequency-alkaline and steam explosion pretreatments - Iroba, Kingsley Lawrence; Tabil, Lope G.; Sokhansanj, Shahab; Venkatesh, Meda (International Journal of Agricultural and Biological Engineering, 2014)
Pelletization, a form of densification, increases bulk density and improves the convenience and accessibility of biomass feedstock due to the uniform shape and size. Pretreatment of biomass enhances the breakdown and accessibility of the cross-linking lignin, which acts as a binding agent. In this study, pelletization of radio frequency-alkaline and steam explosion pretreated barley straw was performed. Three levels of temperature (70oC, 80oC, and 90oC), five levels of the mass ratio of biomass to NaOH solution (1:4, 1:5, 1:6, 1:7, and 1:8), one hour equilibration time, biomass screen size of 1.6 mm, 1% NaOH concentration, and 20 min residence time in the radio frequency chamber were used for the radio frequency-alkaline pretreatment. Three levels of steam temperature (140oC, 160oC, and 180oC), three levels of moisture content of 8%, 30%, and 50% (mass fraction of total mass), and 5 min and 10 min exposure to steam were tested for the steam explosion pretreatment. The effects of both pretreatment methods were evaluated by pelletizing the pretreated and non-pretreated barley straw samples in a single pelleting unit. The pellet density, tensile strength, durability, dimensional stability, and color of the pellets were determined. Radio frequency-alkaline pretreatment with the use of 1% NaOH solution and a ratio of biomass: NaOH solution of 1:8 has significant effect (P<0.05) on the breakdown of the lignified matrix, resulting in pellets with superior physical characteristics. The steam exploded samples pretreated at higher temperatures (180ºC) and retention time of 10 min resulted into pellets with good physical qualities.Keywords: radio frequency, steam explosion, densification, biomass pellets, and alkaline pretreatmentDOI: 10.3965/j.ijabe.20140703.009Citation: Kingsley L. Iroba, Lope G. Tabil, Shahab Sokhansanj, Venkatesh Meda. Producing durable pellets from barley straw subjected to radio frequency-alkaline and steam explosion pretreatments. Int J Agric & Biol Eng, 2014; 7(3): 68－82.